2021
DOI: 10.3389/fpubh.2021.682714
|View full text |Cite
|
Sign up to set email alerts
|

The Contributing Factors of Delayed-Onset Post-traumatic Stress Disorder Symptoms: A Nested Case-Control Study Conducted After the 2008 Wenchuan Earthquake

Abstract: Background: Delayed-onset post-traumatic stress disorder after catastrophes is a major public health issue. However, good designs for identifying post-traumatic stress disorder (PTSD) among earthquake survivors are rare. This is the first nested case-control study to explore the possible factors associated with delayed-onset PTSD symptoms.Methods: A nested case-control study was conducted. The baseline (2011) and follow-up (2018) surveys were utilized to collect data. A total of 361 survivors of the Wenchuan e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…In another study, delayed-onset PTSD symptoms prevalance was found as 9.7% as a result of 7-year long follow up in 340 survivors. While being injured during the earthquake, being unemployed and social support were found to be signi cant for PTSD symptoms in univariate analysis; unemployment was found to be a risk factor and social support was found to be a protective factor for PTSD symptoms in multivariate analysis (7). In the literature, psychological stress was found to be 15.4% with the Professional quality of life (ProQOL) scale as a result of seven years of follow-up after earthquake (29).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In another study, delayed-onset PTSD symptoms prevalance was found as 9.7% as a result of 7-year long follow up in 340 survivors. While being injured during the earthquake, being unemployed and social support were found to be signi cant for PTSD symptoms in univariate analysis; unemployment was found to be a risk factor and social support was found to be a protective factor for PTSD symptoms in multivariate analysis (7). In the literature, psychological stress was found to be 15.4% with the Professional quality of life (ProQOL) scale as a result of seven years of follow-up after earthquake (29).…”
Section: Discussionmentioning
confidence: 93%
“…Several studies investigating the correlation between psychological morbidity and earthquake occurrence have been reported following earthquakes around the world (6). Approximately seventy percent of all earthquake survivors are confronted with traumatic incidences and post-traumatic stress symptoms in their lifetime (7). General Health Questionnaire (GHQ) is extensively used to identify the psychological condition of earthquake survivors as well as the associated factors in order to evaluate the earthquake survivors' state of health.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted on earthquake survivors, it was found that 40.1% of the survivors had post traumatic stress disorder 1 year after the earthquake, while a meta-analysis report found post-traumatic stress disorder with a rate of 29% in the 9-month period following the earthquake among 76,101 individuals [ 7 ]. In Bam province of Iran, psychological distress was measured with GHQ-12 and mental problems were found with a rate of 58%.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, delayed-onset PTSD symptoms prevalance was found as 9.7% as a result of 7-year long follow up in 340 survivors. While being injured during the earthquake, being unemployed and social support were found to be significant for PTSD symptoms in univariate analysis; unemployment was found to be a risk factor and social support was found to be a protective factor for PTSD symptoms in multivariate analysis [ 7 ]. In the literature, psychological stress was found to be 15.4% with the Professional quality of life (ProQOL) scale as a result of seven years of follow-up after earthquake [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation